Small for gestational age: concept, diagnosis and neonatal characterization, follow-up and recommendations - Ignacio Díez López; María Cernada; Laura Galán; Hector Boix; Lourdes Ibañez; Maria L. Couce (Elsevier, 2024)
Newborns who do not reach a weight appropriate for their gestational age and sex can be classified in different ways. This article defines the concepts of small for gestational age (SGA) and intrauterine growth restriction, as well as the underlying causes of these conditions, with the goal of establishing consensus definitions for these patients, in whom treatment with growth hormone throughout childhood may be indicated and who may be at risk of developing endocrine or metabolic disorders in puberty and adulthood. Most SGA children experience spontaneous catch-up growth that is usually completed by age 2 years. In SGA children who remain short, treatment with recombinant human growth hormone is effective, increasing adult height. Small for gestational age infants with rapid catch-up growth and marked weight gain are at increased risk of premature adrenarche, early puberty, polycystic ovary syndrome (girls), insulin resistance and obesity, all of which are risk factors for type 2 diabetes and metabolic syndrome in adulthood. The SGA status can affect different areas of neurodevelopment and manifest at different stages in life; neurodevelopmental outcomes are better in SGA infants with spontaneous catch-up growth. Due to the potential risks associated with SGA, adequate characterization of these patients at birth is imperative, as it allows initiation of appropriate follow-up and early detection of abnormalities. Resumen: Los recién nacidos que no alcanzan un peso acorde con su edad gestacional y sexo se pueden clasificar de distintos modos. En este artículo se definen los conceptos de pequeño para la edad gestacional (PEG) y crecimiento intrauterino reducido, así como las causas que las determinan con el objetivo de consensuar las definiciones en este tipo de pacientes que puedan ser susceptibles de tratamiento con hormona de crecimiento a lo largo de su infancia, así como de desarrollar patología endocrinológica en la pubertad y edad adulta. La mayoría de los niños PEG experimentan un crecimiento recuperador espontáneo que suele completarse a los dos años. En los PEG que no lo realizan, el tratamiento con hormona de crecimiento humana recombinante es efectivo, aumentando su talla adulta. Los PEG con crecimiento recuperador rápido y marcado en peso tienen mayor riesgo de desarrollar adrenarquia precoz, pubertad adelantada, síndrome del ovario poliquístico (niñas), resistencia a la insulina, y obesidad; predisponiendo al desarrollo de diabetes tipo 2 y síndrome metabólico en la edad adulta. La condición de PEG puede afectar diferentes áreas del neurodesarrollo y manifestarse éstas en diferentes etapas de la vida; los PEG con crecimiento recuperador espontáneo tienen mejor pronóstico neurológico. Los posibles riesgos descritos asociados a la condición de PEG hacen imperativo la adecuada caracterización de estos pacientes al nacimiento, que permitirá su seguimiento prospectivo y la detección precoz de alteraciones.